2019
DOI: 10.1155/2019/1609234
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations on Charging/Discharging Performance of a Novel Truncated Cone Thermal Energy Storage Tank on a Concentrated Solar Power System

Abstract: Developing a concentrated solar power (CSP) technology is one of the most effective methods to solve energy shortage and environmental pollution all over the world. Thermal energy storage (TES) system coupling with phase change materials (PCM) is one of the most significant methods to mitigate the intermittence of solar energy. In this paper, firstly, a 2D physical and mathematical model of a novel truncated cone shell-and-tube TES tank has been proposed based on enthalpy method. Secondly, the performance duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Mao et al numerically investigated a novel truncated cone thermal energy storage unit with phase change material. This study has shown a significant decrease in the charging/discharging time in the case of truncated cone TES geometry compare to cylindrical TES [3]. Pourakabar and Darzi [4] numerically studied the possibility of heat transfer enhancement during the melting and solidification process in a cylindrical thermal energy storage unit.…”
Section: Introductionmentioning
confidence: 93%
“…Mao et al numerically investigated a novel truncated cone thermal energy storage unit with phase change material. This study has shown a significant decrease in the charging/discharging time in the case of truncated cone TES geometry compare to cylindrical TES [3]. Pourakabar and Darzi [4] numerically studied the possibility of heat transfer enhancement during the melting and solidification process in a cylindrical thermal energy storage unit.…”
Section: Introductionmentioning
confidence: 93%
“…The heat energy (Q 2c ) gained by the PCM2 in the room model during the charging cycle represents the energy saving of PCM2, and can be estimated as follows [17]:…”
Section: Charging and Discharging Of Pcm Analysismentioning
confidence: 99%
“…A significant improvement in heat exchanger performance and a reduction in PCM melting time in the range of 27-46% were obtained with the change in heat transfer fluid temperature from 60 to 80 • C. The numerical modelling of charging and discharging cycles of phase change materials integrated with air heaters and solar systems is covered in several studies [17][18][19][20][21][22]. The charging and discharging behavior of different phase change materials placed in capsules with various geometries is simulated using computational fluid dynamic (CFD) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bayon [6] presented a brief review on advanced phase change materials for thermal storage. Furthermore, as opined by Mao et al [7], the effective expansion of a low-carbon economy has appeared an imperative option for creating a win-win condition of economic implementation and environment conservation across the world. PCMs-type cooling has been promoted as a successful solution because it can capture heat through devices and machines and store it for later application, including heating houses and offices [8].…”
Section: Introductionmentioning
confidence: 99%